Non‐dissecting large thoracic aortic aneurysm leading to chronic aortic insufficiency presenting as acute heart failure. Issue 8 (15th August 2021) - Bae, Ju Young; Teng, Catherine; Hussein, Khalil I.; Steinhardt, Meyer J.; Howes, Christopher
Abstract: Large, non‐dissecting thoracic aortic aneurysms (TAA) up to 13 cm in size are typically found in elderly patients with non‐specific respiratory symptoms yet must be detected quickly due to their mortality risk. We present a 31‐year‐old man with exertional dyspnea secondary to aortic insufficiency from a 9.4 cm TAA. Abstract : Guidelines vary recommendations for managing thoracic aortic aneurysms (TAAs) according to size, risk factors, and symptoms, but large TAAs in younger patients require shared decision‐making regarding genetic testing and type of surgical procedure.